Rice value chain development in Fogera woreda based on the IPMS experience - Gebey, T.; Berhe, Kahsay; Hoekstra, Dirk; Alemu, B. (International Livestock Research Institute, 2012)
Rice was a staple food crop for more than half of the world’s population. The Asian rice, Oryza sativa and African rice O. glaberrima were the two most cultivated species. The discovery of wild rice in the Fogera plain in the early 1970s was the basis for rice introduction in the woreda as well as in the Amhara region. In the early 1980s through the technical support of North Korean experts, rice cultivation in the seasonally flooded plains started as a pilot in Jigna and Shaga cooperatives in Dera and Fogera woredas, respectively. By 2004, through various development activities, the rice production area had increased to about 6000 hectares. In the rapid rural appraisal conducted by IPMS and various stakeholders in 2004/05, farmers in seasonally flooded areas wanted to increase their rice acreage by addressing bottlenecks in the value chain, in particular excessive weed growth. At the same time farmers in the upland areas were also interested in introducing rice into their farming system. During the intervention period, the price of rice tripled, which further stimulated the interest in rice production. In 2010, the rice area had increased to around 15,500 ha, of which over 5000 ha was in the uplands. This increase has also contributed significantly to employment opportunities for weeding due to area expansion and increased weeding intensity. Project efforts concentrated on the testing/introduction of upland varieties New Rice for Africa (NERICA) and its seed system to complement the already existing X-Jigna variety, commonly used in Fogera. While seed multiplication has been started, further development of the upland varieties in Fogera should be carefully monitored. Data clearly indicated that most farmers have used the X-Jigna variety to expand rice into in the upland system, probably because of better yield potential, especially at times and locations when/where water availability was not limited. Following the increase in rice production, private traders and processors responded by increasing their capacity in terms of number of grinding mills. It was observed that now over 70% of the rice produced was sold as white rice outside the woreda. As a result of this, many processing/marketing challenges need to be addressed. First of all, the issue of grain breakage during processing has to be tackled to improve quality—this issue, was less important in the past when most grain was processed into flour for making injera. Differences in breakages have been observed between the NERICA and X-Jigna varieties, which require adjustments in processing. Also, consumer preferences in urban centres should be considered since X-Jigna has stickiness characteristics as compared to the NERICA varieties. Rice straw and industrial by-products like hulls and bran were becoming increasingly important as a source livestock feed and linkages with dairy and fattening in the woreda can be further developed.